Iklan Promosi Soul Puncak Lawang di Kabupaten Agam Provinsi Sumatera Barat - Putri, Occa Rahdatul Oma Elfa; Tarmawan, Irwan (DIVAGATRA - Jurnal Penelitian Mahasiswa Desain, 2021)
The design was motivated by the high potential of Soul Puncak Lawang tourism to be able to enter the wider market. The various potentials and the high number of visits to tourism are points that can be taken into account as steps to enter the national and international markets. Although new visitors come from local areas such as Agam Regency and areas in West Sumatra. So that a good step is to build a product image of the potential possessed by Soul Puncak Lawang in the minds of the public. The method used in the design and writing of information is qualitative analysis. The data obtained comes from journals, books, articles, questionnaires to direct interviews explaining that the natural wealth and potential possessed by Soul Puncak Lawang can be an important indicator in expanding the market. In this design a commercial campaign is considered appropriate to introduce the potential of Soul Puncak Lawang in the minds of the public. Promotional media in the form of video advertisements are expected to be able to attract the attention of the target audience through audio visual so it is easy to remember.